Second malignant neoplasms within 5 years from first primary diagnosis in pediatric oncology patients in Canada: a population-based retrospective cohort study - Ricci, Christina; Subburaj, Divya; Lim, Kate; Shukla, Neetu; Kaur, Jaskiran; Xie, Lin; Laverty, Meghan; Zakaria, Dianne; Pole, Jason; Pelland-Marcotte, Marie-Claude; Barber, Randy; Israels, Sara J.; et al. (Frontiers in Oncology, 2024)
This is a retrospective cohort study of early Second Malignant Neoplasms (SMN) in pediatric oncology patients. Although previous studies provided information on the incidence and risk of SMN in long term survivors of childhood cancer, there is still scarce information known for short term (< 5 years) prognosis. This study aims to assess the incidence, characteristics, management, and outcome of children who develop SMN malignancies within 5 years of diagnosis of their initial cancer. The Cancer in Young People -Canada (CYP-C) national pediatric cancer registry was used and reviewed pediatric patients diagnosed with their first cancer from 2000-2015. A total of 20,272 pediatric patients with a diagnosis of a first malignancy were analysed. Of them, 0.7% were diagnosed with a SMN within the first 5 years following their first cancer diagnosis. Development of a SMN impacted survival, shown by an inferior survival rate in the SMN cohort (79.1%) after three years compared to that of the non-SMN cohort (89.7%). Several possible risk factors have been identified in the study including the use of epipodophyllotoxins, exposure to radiation, and hematopoietic stem cell transplant. This is the first national study assessing the incidence, characteristics, risk factors and outcome of early SMN in Canadian children from age 0-15 from 2000-2015.